ReGARDD (Regulatory Guidance for Academic Research of Drugs and Devices): The evolution of a collaborative regional CTSA-funded forum and website for regulatory support. Issue 1 (26th January 2021) - Brownley, Kimberly A.; Rape, Marie; Wood, Amanda; Dave, Gaurav; Henderson, Chad; Severynse-Stevens, Diana; Zmuda, Mike; Earp, Diane; Moody, Carmella; Kelly-Pumarol, Issis; Andrews, Joseph; Foss, Kristen M.; et al.
Abstract: Availability of trained professionals to assist researchers navigating regulatory pathways for new drug and device development is limited within academic institutions. We created ReGARDD (Regulatory Guidance for Academic Research of Drugs and Devices), a regional forum initially involving regulatory professionals from four Clinical and Translational Science Award (CTSA)-funded institutions, to build and capitalize on local expertise and to develop a regulatory guidance website geared toward academic researchers. Since 2015, members organized 15 forums covering topics such as FDA premarket submissions, gene therapy, and intellectual property for devices and therapeutics. Through user feedback, targeted surveys, and ongoing iterative processes, we refined and maintained a shared regulatory website, which reached 6000+ users in 2019. Website updates improved navigation to drug versus device topic areas, provided new educational content and videos to address commonly asked questions, and created a portal for posting upcoming training opportunities. Survey respondents rated the website favorably and endorsed expanding ReGARDD as a centralized resource. ReGARDD strengthened the regional regulatory workforce, increased regulatory efficiency, and promulgated best organizational and operational practices. Broad-scale deployment of the ReGARDD model across the CTSA consortium may facilitate the creation of a network of regional forums and reduce gaps in access to regulatory support.